Semen analysis and sperm function parameters in patients with infertility in Navi Mumbai and Panvel region - Bhalekar, Surekha; Ganorkar, Shweta; Bhalekar, Hemant; Roplekar, Prakash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Although semen analysis is routinely used to evaluate male partner in infertile couples, infertility and problems of impaired fecundity have been a concern through ages and is also a significant clinical problem today, which affects 8-12% of couples worldwide. Aim of the study was to study different semen parameters in male factor infertility (MFI) and thus increasing the awareness regarding same. Methods: This is cross sectional study conducted between period of September 2016 to December 2018. Semen of 150 patients were studied and results were analysed as per recent WHO (2010) criteria. Results: The present study included 150 patients whose age ranged from 24 to 51 years. Patients were divided into different age groups and sperm count was studied in each group. Abnormal sperm morphology was studied with respect to sperm head, neck, tail defects and combined defects. Sperm deformity index (SDI) and Teratozoospermic index (TZI) were calculated. Other parameters including semen volume, pH, liquefaction time, sperm vitality and motility were also studied which showed significant variations. Conclusions: Although semen analysis is first and most informative investigation for evaluation of male factor infertility, studying individual semen parameters and sperm function and increasing its awareness in general population especially in developing countries is equally important. Besides, it is necessary to acknowledge its limitation with respect to collection, processing, evaluation and biological variation of samples. Also, a normal semen analysis may not prove successful fertility potential of an individual.